Developing capability through peerassisted learning activities among 4thyear medical students and community health workers in community settings - Marietjie van Rooyen; Angelika Reinbrech-Schütte; J Hugo; T Marcus (South African Medical Association, 2017)
Background. The Longitudinal Community Attachment programme for Students (L-CAS) is an activity by means of which each student is exposed to primary healthcare learning and practice in communities. Capability has been described as ‘an integration of knowledge, skills, personal qualities and understanding used appropriately and effectively … but in response to new and changing circumstances’. Within this paradigm, peer-assisted learning (PAL) has been used to support the development of student capability during L-CAS activities.Objective. To evaluate the impact of PAL sessions on student and community health worker (CHW) capability development.Methods. Study participants comprised 4th-year medical students and CHWs. Student data were drawn from the rotation reflective reports (RRRs) and CHW data from semi-structured interviews.Results. The main themes that emerged from the RRRs and interviews were the impact on the personal and professional development of participants; the creation of awareness and understanding of the context of the communities; relationship building; and the impact of peer learning activities on the knowledge, skills and attitudes of participants.Conclusion. In the process of addressing the challenge of preparing capable professionals, PAL was found to be a very effective way of positioning peers in relation to each other as resources. PAL activities enhanced the abilities of students and CHWs to learn from experience and to achieve the goals of critical reflection and experiential learning.